Aktualisasi Nilai Moderasi Beragama Melalui Tradisi Kirab Sedekah Bumi Desa Getas Pejaten - Muna, Sa'adatul; Partono, Partono (Tatar Pasundan: Jurnal Diklat Keagamaan, 2025)
The paper seeks to show how the Kirab Sedekah Bumi tradition exemplifies moderate religious values. The research focuses on how this tradition employs moderate religious principles to promote ecumenical collaboration between Muslims, Christians, and Confucians. This study adopts a qualitative descriptive method using data gathering procedures including observation, interviews, and documentation. Data analysis consists of data gathering, reduction, presentation, and conclusion drawing. The findings reveal that the Kirab Sedekah Bumi tradition does not pose a problem due to differing religious backgrounds.  Instead, it serves as a bridge to unite the diverse community of Getas Pejaten Village, strengthening interfaith brotherhood.  The kirab sedekah bumi tradition fosters moderate religious values such as tolerance, cooperation and mutual assistance, balance between spiritual and social life, gratitude, and appreciation for cultural heritage.